Water Quality Condition From Upstream To Downstream Of Mahakam River, Kutai Kartanegara District, East Kalimantan - SUJIMAN, Sujiman (PT Keberlanjutan Strategis Indonesia, 2023)
This research aims to ascertain the proclivity of waste in the Mahakam River, identify the category of waste that exhibits the potential to cause pollution, and evaluate the pollution index at the designated site. Water samples were collected at five locations along the Mahakam River in Kutai Kartanegara District, from upstream to downstream. The method of data analysis using the arc gisc software and calculation of the pollution index has been modified to comply with the State Minister of Environment's Decree (KEPMEN LH) No. 115 of 2003. The study's findings indicate an upward proclivity in the total Fecal Coliform waste from the upstream to the downstream of the Mahakam River, with a significant increase observed in the Tenggarong Area. The quality of the waste was measured to be 5400 mg/ltr, surpassing the established environmental quality standards. The Mahakam River exhibits high water quality, up to 4.66 mg/ltr above the established environmental quality standards, although Dissolved Oxygen (DO) waste is primarily located in its upper reaches. The Batuk Area is susceptible to a rise in the pollution index due to Dissolved Oxygen (DO) waste. In contrast, Tenggarong Area is prone to an increase in the pollution index owing to the total Fecal Coliform waste. The pollution levels were measured in five distinct locations along the Mahakam River, namely Batuk Village, Muara Muntai Sub-district, Semayang Lake, Kota Bangun Sub-district, Tenggarong Sub-district, and Jembayan Village. The recorded pollution measures for these locations were 0.599, 0.4576, 0.476, 0.589, 0.526, and 0.583, respectively.